Analysis of drug promotional literature and its abidance to WHO guidelines - Jindal, Meenakshi; Choudhary, Priya; Sharma, Rajeev K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug promotional literature (DPL) is used by the pharmaceutical companies for promotion of their drug. It is the commonest source for providing information about the drug to the physician. According to WHO promotional literature should be reliable, truthful, informative, balanced and up to date. Methods: Study was conducted in Department of Pharmacology, Muzaffarnagar Medical College. 200 drug promotional literatures like advertisements published in medical journal, package insert of medicinal products and brochures were collected and analysed according to WHO criteria. Results: Total 200 promotional literatures were analysed. 100 promotional literatures were from the medical journal, 50 were package inserts of medicinal products and 50 were medicinal brochures. On assessing DPL using WHO criteria, all DPL mentioned brand names and dosage form (100%). Most of them published the generic name (98.5%), therapeutic uses (78%), side- effects (75%), dosage regimen (70%), contraindication (62.5%), warnings (55%), drug interaction (54%), precaution (50%), reference to scientific literature (45%), name of manufacture and distributor (99%), address of manufacturer and distributor (50%). Out of 200 DPL only 151 DPL contain references to scientific literature, 88 DPL references were retrievable and 63 were non retrievable. Conclusions: Our study shows although pharmaceutical companies are trying to adhere to the WHO criteria it is not fulfilled. As DPL are an important source of seeking information by the medical practitioner who rely on them to impart treatment to the patient, strict steps to regulate fulfilment of the WHO criteria should be taken by the government and authorities.